China's Outward Foreign Direct Investments and Impact on the World Economy - Yao, Shujie; Wang, Pan.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book studies the impact of China's outward foreign direct investment on the world economy. It uses both case studies and modeling approaches to study how China's investments have affected the rest of the world.
Keywords: Political science; Finance; Political economy; International economics; Development economics; Economic growth; Asia -- Economic conditions; Political Science and International Relations; Political Economy; Economic Growth; Development Economics; International Economics; Finance, general; Asian Economics